Multiyear surveillance of Influenza A virus in wild birds in Portugal - Henriques, Ana Margarida (2011)
This report presents the results of a multiyear (2005 to 2009) study of avian influenza virus (AIV) occurrence in wild birds in Portugal. A total of 5691 samples from wild birds belonging to 13 different orders were examined. Ninety-three samples tested positive for AIV by matrix reverse transcriptase-polymerase chain reaction, giving a total prevalence of 1.63%. Twenty-one viruses were successfully cultured in embryonated chicken eggs, which represent a rate of viral infectivity of 22.6% in the samples. Nine subtypes of haemagglutinin (H1, H3 to H7, H9 to H11) and eight subtypes of neuraminidase (N1 to N4, N6 to N9) were identified in 20 different combinations. The most prevalent subtypes of haemagglutinin detected were H5, H1 and H4, while for neuraminidase subtypes N2 and N6 were the most common. The subtype combinations H4N6 and H1N1 were predominant (15.1%). All H5 and H7 viruses detected in the present study were low pathogenic for poultry as determined by the sequence of amino acids at the cleavage site of haemagglutinin. The full-length nucleotide sequences of five H5, one H7 and five N3 genes were analysed phylogenetically. The Bayesian analysis revealed that all but one of the strains analysed were closely related to isolates detected in the same period in North and Central European countries. Three H5N3 isolates, all from 2007, formed a separate cluster in both H5 and N3 phylogenetic trees. This study provides evidence that various subtypes of AIV, including subtypes H5 and H7, circulate in Portugal, which may pose a risk to industrial poultry.